2011
DOI: 10.1007/s10329-011-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of sleeping sites by a titi group (Callicebus coimbrai) in the Brazilian Atlantic Forest

Abstract: Predation pressure affects most aspects of primate behaviour, and is especially pronounced in the context of the use of sleeping sites, given the vulnerability of the animal at this time. Most small-bodied platyrrhines have highly systematic patterns of sleeping site choice and use. This study analyses the use of sleeping sites by a free-ranging group of titis (Callicebus coimbrai) monitored at a site in Sergipe, Brazil, between July, 2009 and June, 2010. When the subjects approached a sleeping tree their beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Mammals (including other primates), birds and snakes all predate Neotropical primates (Ferrari 2009;Sousa-Alves et al 2011). Five primate-eating felids occur at Jaú (jaguar Panthera onca, jaguarondi Puma yagouaroundi, margay Felis weidii, ocelot Leopardus pardalis, puma P. concolor: Calleia et al 2008), as do tayra (Eira barbara: Mustelidae), and large snakes such as Boa constrictor (both known primate predators: Bezerra et al 2009;Ferrari et al 2004).…”
Section: Avoidance Of Predatorsmentioning
confidence: 98%
“…Mammals (including other primates), birds and snakes all predate Neotropical primates (Ferrari 2009;Sousa-Alves et al 2011). Five primate-eating felids occur at Jaú (jaguar Panthera onca, jaguarondi Puma yagouaroundi, margay Felis weidii, ocelot Leopardus pardalis, puma P. concolor: Calleia et al 2008), as do tayra (Eira barbara: Mustelidae), and large snakes such as Boa constrictor (both known primate predators: Bezerra et al 2009;Ferrari et al 2004).…”
Section: Avoidance Of Predatorsmentioning
confidence: 98%
“…Preference for particular tree species as sleeping sites is common in primates (e.g., Papio cynocephalus [Hamilton, 1982;Markham et al, 2016]; Sapajus apella [Zhang, 1995]; Tarsier spectrum [Gursky, 1998]; Microcebus griseorufus [Génin, 2010]; Callicebus coimbrai [Souza-Alves et al, 2011]; L. sahamalazensis [Seiler et al, 2013a]; Macaca fascicularis [Brotcorne et al, 2014]). Because the likelihood to produce suitable sleeping tree holes varies by tree species, nocturnal lemur species distribution and abundance may be associated with tree hole availability [Ganzhorn and Schmid, 1998;Radespiel et al, 1998;Rasoloharijaona et al, 2003;Seiler et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…For example, greater protection from mosquitos and predation is offered by intact sleeping trees [Anderson, 1998;Day and Elwood, 1999;Di Bitetti et al, 2000;Nunn and Heymann, 2005]. Additional factors that influence primate choice of sleeping trees include food accessibility [Hamilton, 1982;Chapman, 1989;Heymann, 1995;von Hippel, 1998;Wahungu, 2001;Teichroeb et al, 2012;Markham et al, 2016], tree girth [Gursky, 1998;Aguirre et al, 2003;Hankerson et al, 2007;Holmes et al, 2011], percentage of canopy cover [Garcia and Braza, 1993;Bernard et al, 2011;Souza-Alves et al, 2011;Cheyne et al, 2012], tree height [Gursky, 1998;Zhang, 1995;Day and Elwood, 1999;Wahungu, 2001;Peh and Sodhi, 2002;Brotcorne et al, 2014], height of the first branch [Day and Elwood, 1999], status of the tree as alive or dead [Schmid, 1998;Hankerson et al, 2007;Seiler et al, 2013a], and tree species [SouzaAlves et al, 2011;Markham et al, 2016;Salmona et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…are regarded as primarily frugivorous primates that complement their diets with invertebrate prey and other plant parts, such as leaves, seeds and flowers (Bicca-Marques and Heymann, 2013;DeLuycker, 2012;Heymann and Nadjafzadeh, 2013). These primates tolerate disturbed habitat (Heiduck, 2002;Jerusalinsky et al, 2006;Souza-Alves et al 2011a) and it has been suggested already that titi monkeys might show some dietary plasticity. For example, Santos et al (2012) report that C. nigrifrons can take advantage of temporarily available items, such as synchronous production of seed bamboo (=masting bamboos).…”
Section: Luana Vinhas João Pedro Souza-alvesmentioning
confidence: 99%